2016
DOI: 10.1371/journal.pone.0155065
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Homelessness among Older Homeless Adults: Results from the HOPE HOME Study

Abstract: Little is known about pathways to homelessness among older adults. We identified life course experiences associated with earlier versus later onset of homelessness in older homeless adults and examined current health and functional status by age at first homelessness. We interviewed 350 homeless adults, aged 50 and older, recruited via population-based sampling. Participants reported age at first episode of adult homelessness and their life experiences during 3 time periods: childhood (<18 years), young adulth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 43 publications
(59 reference statements)
3
81
0
4
Order By: Relevance
“…A life‐course perspective on homelessness may provide additional explanation for our findings. There is increasing recognition that a large proportion of older homeless adults first became homeless in old age (Brown et al ., ; Crane et al ., ; Shinn et al ., ). Consistent with this finding, our study found that older homeless adults first experienced homelessness at an older age than their younger counterparts.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A life‐course perspective on homelessness may provide additional explanation for our findings. There is increasing recognition that a large proportion of older homeless adults first became homeless in old age (Brown et al ., ; Crane et al ., ; Shinn et al ., ). Consistent with this finding, our study found that older homeless adults first experienced homelessness at an older age than their younger counterparts.…”
Section: Discussionmentioning
confidence: 97%
“…Cohen's model of aging and homelessness proposes that risk factors for homelessness such as low income and poor social support (Cohen, ) can accumulate over the life course. A triggering event later in life, such as loss of employment or death of a spouse (Brown et al ., ; Crane et al ., ), can precipitate homelessness in people who have lived in stable housing for most of their lives.…”
Section: Discussionmentioning
confidence: 99%
“…42, 43 Adults who become homeless earlier in life tend to have more early life adverse experiences such as mental health, imprisonment, and substance use. 44 It is possible that the association between suspension or expulsion from school and greater severity illicit drug and alcohol use is a reflection of the impact of early life experiences on the development of substance use later in life.…”
Section: Discussionmentioning
confidence: 99%
“…This outreach approach expanded on prior methods (Burnam and Koegel, 1988) to include homeless encampments and recycling centers to ensure inclusion of unsheltered adults. We recruited individuals from all overnight homeless shelters in Oakland that served single adults, all free and low-cost meal programs that served homeless persons ≥3 prepared meals a week, a recycling center, and places where unsheltered people stay overnight (Brown et al, 2016a; Lee et al, 2016a). Individuals were eligible to participate if they spoke English, were homeless as defined by the federal Homeless Emergency Assistance and Rapid Transitions to Housing (HEARTH) Act (2010), and were aged ≥50.…”
Section: Methodsmentioning
confidence: 99%